Catalytic Combustion of Vinyl Chloride Emission over a TiO2–MnOx Catalyst. (September 2017) - Wan, Yiling; Xie, Xiangyu; Chen, Xiaojun
TiO2 –MnO x catalyst samples with different Ti/(Ti + Mn) molar ratios (2:3, 3:4, 4:5, 5:6, 6:7 and 1) prepared by the citric acid (CA) sol-gel method were studied in the catalytic combustion of vinyl chloride (VC) emission. The effects of preparation conditions and operation parameters on the catalytic performance of TiO2 –MnO x were investigated. The catalyst samples were characterised by N2 adsorption, X-ray diffraction (XRD) and H2 -temperature programmed reduction (H2 -TPR). In the catalytic combustion of VC over TiO2 –MnO x, products containing HCl, CO2, and H2 O were obtained and there were no by-products such as chlorohydrocarbons and chlorine. The TiO2 –MnO x catalyst with the molar ratio of CA/Mn/Ti = 0.30:0.20:0.80 showed the best catalytic performance and had better operating flexibility over the ranges of gas hourly space velocity (GHSV) of 15000–100000 h −1 and VC concentration of 0.05–2.00%. The temperatures at 50% conversion (140 °C) and at 99% conversion (220 °C) were achieved at a VC concentration of 0.1% and GHSV of 15000 h −1 . XRD characterisation indicated that only the characteristic diffraction peaks of TiO2 with the anatase structure appeared and no characteristic diffraction peaks of MnO x species appeared for the TiO2 –MnO x catalyst. XRD and H2 -TPR results indicated that Mn ions were incorporated into the TiO2 lattice to form a Ti–Mn–O solid solution, which enhanced the reactivity of active oxygen species on the catalyst surface and thereby promoted the catalyst activity.